Evolution of External Health Costs of Electricity Generation in the Baltic States - Lu, Jintao; Zhang, Chong; Ren, Licheng; Liang, Mengshang; Strielkowski, Wadim; Streimikis, Justas (International journal of environmental research and public health, 2020)
Implementation of strict policies for mitigating climate change has a direct impact on public health as far as the external health costs of electricity generation can be reduced, thanks to the reduction of emission of typical pollutants by switching to cleaner low carbon fuels and achieving energy efficiency improvements. Renewables have lower external health costs due to the lower life cycle emission of typical air pollutants linked to electricity generation, such as SO2, NOx, particulate matter, NH3, or NMVOC (Non-methane volatile organic compounds), which all appear to have serious negative effects on human health. Our case study performed in the Baltic States analyzed the dynamics of external health costs in parallel with the dynamics of the main health indicators in these countries: life expectancy at birth, mortality rates, healthy life years, self-perceived health, and illness indicators. We employed the data for external health costs retrieved from the CASES database, as well as the health statistics data compiled from the EUROSTAT database. The time range of the study was 2010-2018 due to the availability of consistent health indicators for the EU Member States. Our results show that the decrease of external health costs had a positive impact on the increase of the self-perceived good health and reduction of long-standing illness as well as the decrease of infant death rate. Our conclusions might be useful for other countries as well as for understanding the additional benefits of climate change mitigation policies and tracking their positive health impacts. The cooperation initiatives on clean energy and climate change mitigation between countries like One Belt One Road initiative by the Chinese government can also yield additional benefits linked to the public health improvements.
Keywords: elektřina; dynamics; pobaltské republiky; Electricity; health indicators; znečištění ovzduší; Baltic States; Air Pollution; electricity generation; látky znečišťující vzduch; Air Pollutants; Particulate Matter; Health Care Costs; náklady na zdravotní péči; external health costs; pevné částice